Alkaline Phosphatase Levels as a Predictor of Neonatal Hyperbilirubinemia - Rani Saba Urooj, Nayab Butt, Sikander Ikram, Fatima Tahira, Noor-Ul-Ain Mehak, Rana M.Umair, Talha Laique (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Jaundice is a common health issue especially in pediatric practice. It can be physiological or pathological hence has supreme importance clinically. Aim: To determine the accuracy of cord blood alkaline phosphatase levels for predicting neonatal hyperbilirubinemia. Study Design: Descriptive case series. Methodology: It was conducted at Department of Pediatrics, Sir Ganga Ram Hospital-Lahore. All neonates fulfilling the inclusion criteria were enrolled. Their demographic information, gestational and birth history was taken. Cord blood sample (5ml) was taken and measured for ALP level and total bilirubin level. Statistical analysis: Data analyzed by using SPSS 23. Chi-square was applied. Results: Predictive accuracy of cord blood ALP level for predicting neonatal hyper-bilirubinemia showing sensitivity and specificity as 91.60% and 93.04 respectively. Conclusion: It was concluded that predictive accuracy of cord blood alkaline phosphatase level is good and reliable for predicting neonatal hyperbilirubinemia.